Vestibule-Middle Ear Dehiscence Tested With Perilymph-Specific Protein Cochlin-Tomoprotein (CTP) Detection Test - Fujita, Takeshi; Kobayashi, Takaaki; Saito, Kazuya; Seo, Toru; Ikezono, Tetsuo; Doi, Katsumi (Frontiers in Neurology, 2019)
An 8-year-old boy was referred to the ENT department for further evaluation of right-sided conductive hearing loss. A small cyst anterior to the oval window and fixation of the stapes footplate were observed during an exploratory tympanotomy. The concentration of a perilymph-specific protein, cochlin-tomoprotein (CTP), in the middle ear lavage fluid was measured with an ELISA-based CTP detection kit. The level of CTP in the middle ear lavage fluid before fenestration of the cyst was 0.26 ng/ml (negative), and its level after fenestration was 2.98 ng/ml (positive), confirming the presence of perilymph in the cyst. A small bone dehiscence, considered to be the fissula ante fenestram, was observed anterior to the stapes footplate after removal of the cyst. The CTP detection test results allowed us to confirm that the small bone dehiscence was connected to the inner ear.